2000
DOI: 10.1034/j.1600-0749.13.s8.25.x
|View full text |Cite
|
Sign up to set email alerts
|

UVA, Pheomelanin and the Carcinogenesis of Melanoma

Abstract: Cloudman S91 mouse melanoma cells vary in constitutive and inducible melanin levels. Survival, mutation induction and DNA damage were quantitated after exposure to UVB, UVA and FS20 lamps. Assuming that the observed differences are related to melanin, induced pigment is photo-protective for survival and mutation after UVB and FS20 exposure, and is photosensitizing for survival after UVA exposure. No changes in pyrimidine dimers could be measured. DNA damage in pigmented mouse melanocytes (melan-a and melan-b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 21 publications
3
90
0
1
Order By: Relevance
“…In humans, large amounts of pheomelanin and small amounts of eumelanin are characteristic of red hair, fair skin, freckling, and green irides [25], phenotypes that are more common at high latitudes [10]. If the removal of excess cysteine has adaptive value, this should be reflected in human pigmentation patterns.…”
Section: Implications For Understanding Human Pigmentation Patternsmentioning
confidence: 99%
See 3 more Smart Citations
“…In humans, large amounts of pheomelanin and small amounts of eumelanin are characteristic of red hair, fair skin, freckling, and green irides [25], phenotypes that are more common at high latitudes [10]. If the removal of excess cysteine has adaptive value, this should be reflected in human pigmentation patterns.…”
Section: Implications For Understanding Human Pigmentation Patternsmentioning
confidence: 99%
“…It has also been reported that more-pheomelanic individual barn owls (Tyto alba) are particularly sensitive to physiological stress caused by corticosterone compared to less-pheomelanic birds [7], and that tawny owls Strix aluco belonging to the pheomelanic morph have lower viability during adverse environmental conditions than conspecifics belonging to the eumelanic morph [8]. In humans and mice, pheomelanin increases the photosensitization of cells to UVinduced oxidative damage [9], its content being positively related to cancer risk in humans [10]. Overall, these results indicate that pheomelanin is a limiting pigment that may have important evolutionary consequences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimal receptor activity, as in red hair/fair skin polymorphisms, produces the red/yellow pheomelanin pigment, whereas increasing MC1R activity stimulates the production of black/brown eumelanin (Valverde et al, 1995). Pheomelanin has weak UVR shielding capacity relative to eumelanin, and has been shown to amplify UVA-induced ROS reactive oxygen species) (Rouzaud et al, 2005, Wenczl et al, 1998Hill and Hill, 2000). Unlike non-melanoma skin cancers, melanoma is not restricted to sun-exposed skin and ultraviolet radiation signature mutations are infrequently oncogenic drivers (Curtin et al, 2005).…”
Section: Susceptibilitymentioning
confidence: 99%